MODEL OF THE COMPLEX ANALYSIS OF FIXED ASSETS IN THE ENTERPRISE MANAGEMENT SYSTEM - Savkiv , U.S.; Vasylyuk М.М.; Leshchuk , H.V. (The actual problems of regional economy development, 2023)
The article is aimed at improving the process of the state analysis and the effectiveness of the use of fixed assets at the enterprise. The practice of a modern enterprise management requires an accurate operative evaluation and the complex analysis of processes related to the restoration of fixed assets. The proposed model of the analysis of fixed assets at the enterprise facilitates the possibility to carry out an effective and sound analysis of existing fixed assets with the purpose of effective management by them. The algorithm of actions of an analyst and the stages sequence of complex analysis of fixed assets at the enterprise were worked out using the technical suitability coefficients of fixed assets and the technical suitability of equipment at the enterprise. The purpose of the article is to develop a model of complex analysis of fixed assets on the basis of their technical suitability coefficients and the technical suitability of equipment at the enterprise, which allows to improve processes of the state analysis and effectiveness of use of fixed assets. To achieve the set goal, the following methods of research such as deduction– for determining the main advantages and disadvantages of the indicators application of the state analysis and effectiveness of the use of fixed assets, systematic analysis – for studying accounting processes in their relationships and interdependency, synthesis and complex approach – for forming a complex model of analysis of fixed assets, coefficient method – for application of coefficients of complex analysis of fixed assets and the method of abstractions – for forming the generalized conclusions were used in this article. The current methodology of analysis of the efficiency of the use of fixed assets as well as their operation and updating at the enterprise is considered, grouping indicators that determine the state and effectiveness of the use of fixed assets was conducted, the model of complex analysis of fixed assets has been developed and the directions of complex analysis of fixed assets have been determined in this article. The scientific novelty of the research is the implementation of the complex approach to the analysis of fixed assets on the basis of the corresponding coefficients of technical suitability of fixed assets and the technical suitability of the equipment at the enterprise, which allows for improving the processes of analyzing the condition and effectiveness of the use of fixed assets, as well as using certain universal analytical indicators will ensure the analysis of the use effectiveness of certain fixed assets in order to increase their efficiency. The results of the scientific research can be applied by enterprises in the system of the analysis of the state and reproduction of fixed assets.